THERMAL ANALYSIS OF A PENTAGONAL SOLAR AIR COLLECTOR - ABO, ODAY ADNAN; HASSAN, LOKMAN H (Journal of Duhok University, 2017)
In this paper, a pentagonal shaped Solar Air Collector (SAC) is proposed. The pentagon design is used to improve the incident radiation angle. The SAC is tested in University of Duhok campus, Kurdistan Region, Iraq in a stand facing south. The absorber made from the sandwich steel panel plate with an area of 0.9*1.5 m2 and thickness of 0.4 mm. The collector is covered with a Plexiglas of thickness 5 mm. The effect of the air flow channel on the collector efficiency is studied. Experimental studies are carried out for different tilt angles to show the improvement in the collector performance. The collector is tested for four sunny days in the same atmospheric conditions in December as the worst month. The results demonstrate that the optimum tilt angle of the day will substantially enhance the thermal efficiency comparing to latitude tilt angle. In addition, the proposed SAC with closed channel and open channel shows different performance during the day time.